The Color in F. M. Dostoevsky Novel Netochka Nezvanova - Pavel A. Ivanov (Russian Academy of Sciences. A.M. Gorky Institute of World Literature, 2019)
The article concerns colors and their role in Dostoevsky's novel Netochka Nezvanova. Different colors of characters or objects are often noticed by the author. Every color has its unique significance, meaning, so its analysis in different contexts is required for entire understanding of the author’s position.